Ameliorative action of “daitongxiao” against hyperuricemia includes the “uric acid transporter group” - Zheng, Lijie; Bai, Yuanmei; Wan, Yan; Liu, Feifan; Xie, Yuhuan; He, Jinglin; Guo, Peixin (Frontiers in Pharmacology, 2024)
This study aimed to investigate the potential mechanisms involved in the therapeutic effects of daitongxiao (DTX) on hyperuricemia (HUA). DTX was administered to the following two animal models of HUA via gavage feeding: HUA quail model (a uricotelic animal with urate oxidase deficiency), treated continuously for 35 days post-HUA induction; HUA rats (an animal with active urate oxidase), treated continuously for 28 days post-HUA induction. HUA was induced in quail by gavage feeding a solution of sterile dry yeast powder, while that in rats was induced by intragastric gavage feeding a solution of adenine and ethambutol hydrochloride. DTX improved overall health, increased bodyweight, reduced renal index, serum urate levels, serum xanthine oxidase activity, blood urea nitrogen, and creatinine, and enhanced urinary and fecal uric acid (UA) excretion in these two animal models. The results of hematoxylin and eosin and silver hexamine silver staining of kidney sections revealed that DTX significantly mitigated HUA-induced renal structural damage and inflammatory response. The results of quantitative real-time polymerase chain reaction, western blotting, and immunofluorescence analyses revealed that DTX downregulated the renal expression levels of glucose transporter 9 (GLUT9) and upregulated the renal expression levels of organic anion transporters (OAT1 and OAT3) in both HUA models. Thus, the findings of this study suggest that DTX suppresses the progression of HUA by modulating the expression of the UA transporter group members.